A new approach to determining the performance of superdisintegrants. (January 2015) - Joshi, Yogesh; Mastropietro, David; Muppalaneni, Srinath; Omidian, Hossein
Superdisintegrants are used in some tablet formulations to improve water penetration and disintegration, leading to improved drug dissolution rates. The extremely fast speeds at which superdisintegrants perform their functions have made it difficult to evaluate differences in their disintegration properties. In this study, a novel technique was developed and explored to measure the swelling pressure of superdisintegrants under compressed conditions. The measurement of swelling pressure was chosen as it is not directly dependent on the mechanisms involved in tablet disintegration (swelling, wicking, and deformation). Three commercial superdisintegrants including Ac-Di-Sol ® (internally crosslinked carboxymethylcellulose), Explotab ® (internally crosslinked carboxymethylstarch), and Polyplasdone ® XL (crosslinked polyvinylpyrrolidone) were evaluated using this technique as well as free swelling and videography. Swelling pressure was found to easily discern the differences among the superdisintegrants that the other methods could not. The swelling data were also found to be compatible with an equation used to describe water absorption behavior into hydrogels with derived factors being comparable to those observed experimentally. Therefore, an easy and effective method to evaluate the swelling behavior of superdisintegrants was obtained by combining the swelling model and the swelling pressures by this technique.